Human capital to be create of company performance prove goal orientation to organizational culture as an approach - Miftahul Jannah S (Institute of Computer Science (IOCS), 2024)
Human resources are assets or capital that continue to develop over time and business dynamics as well as developments in technology and science. This research aims to describe the application and achievements of human capital that have been implemented in recent years as an effort to improve performance with evidence of goal orientation, as well as examining the relationship between the application of human capital and performance with evidence of goal orientation. This research uses a quantitative method with a descriptive approach, by taking purposive sampling from 74 employees who hold supervisory positions at PT AIM Biskuit Sidoarjo, East Java. Data was collected through questionnaires and inferential statistical analysis was carried out. The research results can illustrate that the more optimal the application of human capital as an HR development strategy is, the greater the performance will prove to be the goal orientation, and vice versa. This is known from cross distribution analysis with a value of ?2 = 104.128, with a probability of 0.000 (p<0.05); then the results of this research also prove that there is a dignified positive relationship between human capital and performance, proving goal orientation from the value of r = 0.858 with p = 0.000 (p <0.05); whose coefficient of determination value explains that human capital is able to contribute 73.7% to increased performance as evidenced by goal orientation